Furniture design : Television cabinet using recycle materials (solid wood waste) / Syazwan Iza - Iza, Syazwan (Faculty of Applied Sciences, 2016)
The purpose of the study is to design and produce a television cabinet using recycle materials (solid wood wastes). This is to ensure the using of green wood can be reduced by utilizing solid wood waste as available raw material. The design of this furniture is only customized for television cabinet whereas the final user able to understand what is the purposed of this product. This has been proved that television cabinet using recycled material (solid wood waste) was successfully made. 100 correspondences were given questionnaire and majority of the correspondences rate this product as can be commercialized and promoted to the market. As the majority of the rating is being rated at moderated by all correspondences thus it can be accepted that this television cabinet using recycle material have the potential to replaced furniture that is made from green wood.